ANALYSIS OF INFLUENCE OF QUICK RATIO, TOTAL ASSET TURN OVER, AND DEBT TO EQUITY TO PROFITABILITY (EMPIRICAL STUDIES AT IDX-LISTED MANUFACTURING COMPANIES at 2017-2019) - Widia Anggraini; Arisman Arisman (Journal Competency of Business, 2021)
Profitability is a tool used to analyze management performance, the level of profitability will describe the company's profit position. Profitability ratio is the ratio used in assessing a company's capacity to earn profits based on its normal business activities. This study aims to determine the effect of the quick ratio, total asset turnover, and debt to equity on profitability. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The companies sampled in this study were 34 manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used by researchers is non probability sampling with purposive sampling technique. This study uses a quantitative approach with data processing using the SPSS 25 for windows application. The results of this study indicate that, (1) the quick ratio has a positive effect on return on equity, this is indicated by a significant value of 0.019 which means less than α = 0.05 with a coefficient value of 2.397. (2) total asset turnover has a positive effect on return on equity, this is indicated by a significant value of 0,000 which means it is smaller than α = 0.05 with a coefficient value of 2.184. (3) debt to equity has a negative effect on return on equity, this is indicated by a significant value of 0.008 which means it is smaller than α = 0.05 with a coefficient value of -2.762.